2018
DOI: 10.1029/2018ja025575
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle Response of CO2 Over the Austral Winter Mesosphere and Lower Thermosphere Region

Abstract: This work uses Sounding of the Atmosphere using Broadband Emission Radiometry CO2 data from 2002 to 2015 and Specified Dynamics‐Whole Atmosphere Community Climate Model (SD‐WACCM) outputs from 1979 to 2014 to show, for the first time, the solar cycle response of CO2 in the Austral winter mesosphere and lower thermosphere region. Both Sounding of the Atmosphere using Broadband Emission Radiometry and SD‐WACCM show that CO2 experiences a decrease during solar maximum throughout the Austral winter mesosphere and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…It becomes complicated to determine what processes (i.e., dynamical vs. chemical) contribute mostly to the observed ozone 11‐year variation, despite the clear in‐phase correlation with the solar cycle. Salinas et al () showed that k zz may have an 11‐year variation, which can in turn modulate the [O] and [CO] concentrations and subsequently nighttime [O 3 ] in the UMLT. If the solar cycle variation of nighttime [O 3 ] were dominated by chemical processes, one would expect its 11‐year amplitude to be proportional to its background mean.…”
Section: Discussionmentioning
confidence: 99%
“…It becomes complicated to determine what processes (i.e., dynamical vs. chemical) contribute mostly to the observed ozone 11‐year variation, despite the clear in‐phase correlation with the solar cycle. Salinas et al () showed that k zz may have an 11‐year variation, which can in turn modulate the [O] and [CO] concentrations and subsequently nighttime [O 3 ] in the UMLT. If the solar cycle variation of nighttime [O 3 ] were dominated by chemical processes, one would expect its 11‐year amplitude to be proportional to its background mean.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ~11 year cycle of the atmospheric circulation may be due to changes in CO 2 . Salinas et al showed that CO 2 decreases during solar maxima throughout the Austral winter mesosphere and lower thermosphere region [45]. This does not lead to enhanced atmospheric circulation in these regions during years with high solar activity.…”
Section: Discussionmentioning
confidence: 98%
“…They also indicated that the results were in excellent agreement with other analyses of observations. Based on SD-WACCM simulations, Salinas et al [45] identified the solar cycle response of CO 2 in the lower thermosphere via modulations of the circulation in the lower thermosphere. This discovery was also demonstrated using the satellite observations.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation